2017
DOI: 10.1089/hs.2016.0124
|View full text |Cite
|
Sign up to set email alerts
|

Web-Based Surveillance of Illness in Childcare Centers

Abstract: School absenteeism is an inefficient and unspecific metric for measuring community illness and does not provide surveillance during summertime. Web-based biosurveillance of childcare centers may represent a novel way to efficiently monitor illness outbreaks year-round. A web-based biosurveillance program ( sickchildcare.org ) was created and implemented in 4 childcare centers in a single Michigan county. Childcare providers were trained to report sick children who required exclusion or had parent-reported abse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 32 publications
0
9
1
1
Order By: Relevance
“…Natalie S. and Collins A. in the article, Web-based Surveillance of Illness in Childcare Centers, made a proposal for active bio-surveillance in childcare centers [11]. The authors were of the opinion that monitoring childcare centers for disease outbreak was more effective than the traditional method of monitoring schools only.…”
Section: Web-based Disease Surveillance and Epidemic Alert System: Stmentioning
confidence: 99%
“…Natalie S. and Collins A. in the article, Web-based Surveillance of Illness in Childcare Centers, made a proposal for active bio-surveillance in childcare centers [11]. The authors were of the opinion that monitoring childcare centers for disease outbreak was more effective than the traditional method of monitoring schools only.…”
Section: Web-based Disease Surveillance and Epidemic Alert System: Stmentioning
confidence: 99%
“…B. über das amtliche Meldesystem, oder weniger spezifische, aber sensitivere Indikatoren, die Symptome bzw. Syndrome oder Abwesenheiten erfassen und damit ermöglichen, die generelle Dynamik oder gar Ausbruchsgeschehen frühzeitig zu erkennen [ 7 , 8 ]. Da Übertragungen in Kitas eine Epidemie verstärken (amplifizieren) können, wird z.…”
Section: Introductionunclassified
“…4 A study that analyzed a web-based biosurveillance program in 4 childcare centers in a single Michigan county found that 46% of the 385 individual episodes of fever, gastroenteritis, influenza like illness, cold, rash, conjunctivitis, ear infection occurred with preschoolers. 5 Therefore, interventions to promote healthy behaviors among children and staff of childcare educational settings in order to decrease the incidence of infectious diseases, such as respiratory infection and diarrhea, 6 remains needed.…”
Section: Introductionmentioning
confidence: 99%